An experimental investigation on transpiration cooling with phase change under supersonic condition. (25th July 2016) - Shen, Lin; Wang, Jianhua; Dong, Wenjie; Pu, Jian; Peng, Jinlong; Qu, Dejun; Chen, Lianzhong
Abstract : Highlights: High effect of transpiration cooling using water is verified in supersonic condition. Overcooling and ablation can be solved by controlling temperature and pressure of chamber. Zirconia TBC offers a quite effective protection for impermeable alloy. A numerical approach to estimate water consumption is introduced. Abstract: The extremely high heat loads on hypersonic vehicles make great challenges for the research and development of more effective Thermal Protection Technique (TPT). Transpiration cooling using liquid coolant has been confirmed as a promising TPT, because the phase change of liquid can release a large amount of latent heat. An experimental investigation on transpiration cooling using water as coolant was conducted in the arc-heated wind tunnel of China Academy of Aerospace Aerodynamics (CAAA), with a free stream specific enthalpy, mass flow rate and Mach number of 2700 kJ/kg, 645 g/s and 4.2, respectively. The specimen used in this experiment, a nose cone, consists of two types of materials. One is sintered porous material in the leading edge region as transpiration cooling matrix, and the other is impermeable alloy with zirconia Thermal Barrier Coating (TBC). The thermodynamic and aerodynamic parameters in coolant chamber are controlled by a quantitative injector of coolant mass flow rate to prevent the phenomena of overcooling and ablation. Surface temperature distributions are captured by an infrared thermal imaging system (ITIS). This paper exhibits and analyzes some interesting experimental phenomena, including ice formation in high enthalpy environment, hysteresis of thermal balance due to TBC, and variations of surface cooling effectiveness. A numerical approach to estimate the water mass flow rate is introduced and the relative error referenced experimental results is analyzed.